Russian System of Foreign Policy Expertise - A. A. Varfolomeev; O. P. Ivanov; I. V. Surma; Yu. A. Trefilova (Vestnik MGIMO-Universiteta)
Abstract: The article considers the system of foreign policy expertise as an independent subject of research. The authors note the positive aspects of competitive analysis of the external nvironment, which allows one to level out the asymmetry of political and economic cultures within a given country, as well as to smooth out the personal interests. This ensures a variability of approaches in foreign policy decision-making, which ultimately contributes to the promotion of balanced national interests. The North American approach differs in preferences, methodological trends, forms of theoretical ethnocentrism and various forms of social construction. The European scholars and experts in foreign policy analysis use the theory of international relations much more extensively than their North American counterparts.Based on the analysis, we propose to use a comprehensive integrated method, developed in the Russian Diplomatic Academy, using an interdisciplinary approach based on elements of political psychology, sociology of management, international law, structural, functional and institutional approaches, etc. We also propose to use virtual cognitive centers and methodologies, which not only contain a specific sequence of stages of predicting the development of the international situation, but also provide an opportunity to choose methods of Foresight, taking into account the existing time, human resources and financial constraints, and the possibility of their adaptation to the applied tasks of analytical and prognostic activities of federal authorities in the field of foreign policy.